Rescue Balloon Pulmonary Angioplasty in a Rapidly Deteriorating Chronic Thromboembolic Pulmonary Hypertension Patient with Liver Failure and Refractory Infection. (1st March 2014) - Tsuji, Akihiro; Ogo, Takeshi; Demachi, Jun; Ono, Yusuke; Sanda, Yoshihiro; Morita, Yoshihiro; Fukuda, Tetsuya; Nakanishi, Norifumi
Abstract : Pulmonary endarterectomy (PEA) is the standard therapy for chronic thromboembolic pulmonary hypertension (CTEPH). Balloon pulmonary angioplasty (BPA) is an alternative therapy for such patients. Here we report the case of a 60‐year‐old woman who presented with severe CTEPH resulting in low cardiac output and liver failure. Her clinical status rapidly deteriorated after she developed a respiratory infection that was refractory to antibiotic treatment. PEA was risky because of her unstable hemodynamics, uncontrolled infection, and liver failure with jaundice. We thus performed rescue BPA. After 3 BPA procedures, her cardiac symptoms improved from World Health Organization functional class IV to II, and her jaundice resolved. The day after her final BPA procedure, her hemodynamics dramatically improved, and she continued to show improvement 3 months later. We thus suggest that BPA is a good treatment option in CTEPH patients with rapidly deteriorating heart failure and uncontrolled comorbidities.